Integrating the tumor-suppressive activity of Maspin with p53 in retuning the epithelial homeostasis: A working hypothesis and applicable prospects - Tang, Sijie; Ling, Zhongli; Jiang, Jiajia; Gu, Xiang; Leng, Yuzhong; Wei, Chaohui; Cheng, Huiying; Li, Xiaohua (Frontiers in Oncology, 2022)
The epithelial malignant transformation and tumorous development were believed to be closely associated with the loss of its microenvironment integrity and homeostasis. The tumor suppressive molecules Maspin and p53 were demonstrated to play a crucial role in body epithelial and immune homeostasis. Down regulation of Maspin and mutation of p53 were frequently associated with malignant transformation and poor prognosis in various human cancers. In this review, we focused on summarizing the progress of molecular network of Maspin in studying epithelial tumorous development and its response to clinic treatment, and try to clarify the underling anti-tumor mechanism. Our hypothesis is that, upon stimulating of cellular stress and by integrating with p53, the aroused Maspin plays the epigenetic surveillant role to prevent epithelial digressional process and retune the epithelial homeostasis, which involved in activating host immune surveillance, regulating the inflammatory factors and fine-tuning its associated cell signaling pathways. Thus, utilization of this hypothesis by reducing cellular stress and mimicking Maspin’s epigenetic regulation activity could achieve the cancer prevention and enhance the chemotherapy efficacy.